A Novel Approach to Brachycephalic Syndrome. 2. Laser‐Assisted Turbinectomy (LATE). Issue 2 (21st January 2016) - Oechtering, Gerhard U.; Pohl, Sabine; Schlueter, Claudia; Schuenemann, Riccarda
Abstract : Objective: To introduce a new surgical procedure based on interventional, laser‐assisted removal of obstructing turbinate tissue to improve endonasal airway patency in brachycephalic dogs and to confirm the short and long term results using computed tomography (CT) and rhinoscopy. Study Design: Prospective clinical study. Animals: Brachycephalic dogs (n = 158; 70 Pugs, 77 French Bulldogs, 11 English Bulldogs) referred for treatment of severe respiratory distress because of brachycephalic syndrome. Methods: Computed tomography and anterior and posterior rhinoscopy were performed to evaluate endonasal obstruction. Laser‐assisted turbinectomy (LATE) using a diode laser was performed as part of a multilevel surgery. Nasal conchae that were causing airway obstruction were removed. Results: The obstructing parts of the conchae were safely and efficiently removed by LATE, shaping a patent nasal airway in all dogs. The newly developed surgical procedure involved 3 steps: turbinectomy of the (1) concha nasalis ventralis ; (2) rostral aberrantly growing turbinates (RAT); and (3) caudal aberrantly growing turbinates (CAT). Complications of the procedure included transient intraoperative hemorrhage in 51 of 158 dogs (32.3%); however, a temporary tamponade was necessary in only 2/158 dogs (1.3%). After 6 months, regrowth of turbinates required resection of possibly re‐obstructing tissue in 25/158 dogs (15.8%; 1 Pug and 24 French Bulldogs). Conclusion: LATE is an effective method for creating a patent nasal airway in brachycephalic dogs with intranasal obstruction.